Geochemical and Mineralogical Characteristics of Mine Wastes from Gadaeregi Artisanal and Small-Scale Gold Mining Area, North-Central Nigeria: Implications on Human Health - Musa Waziri, Nuhu; Abdullahi, Suleiman (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The chemical and mineralogical characteristics of wastes from artisanal and small-scale gold mining (ASGM) in the Gadaeregi area, Nigeria were assessed to determine their potential human health risks. Mine wastes were sampled and subjected to X-ray diffraction and X-ray fluorescence analyses to enable us assess the human health risk. The results show albite, quartz, actinolite, dolomite and annite as the major phases in the wastes. Fe, Si and Ti are present at concentrations above the upper crustal abundances; while Al, Na, K and Ca are depleted. The wastes are enriched in nine trace elements (Ni, Cu, Ga, V, Cr, Ce, As, Pb and W) and depleted in five others (Ba, Rb, Y, Zr and Nb). Cr, As and Pb are the most dosed trace elements in these wastes for both children and adults for the two exposure scenarios. While all three elements have HQi values of > 1 for children in the ingestion model, only As has a value of > 1 for adults. The inhalation route does not appear to have any potential health effects for both children and adults. The overall hazard index reveals that both children and adults may be vulnerable to adverse non-cancer health effects. However, children appear to be several orders of magnitude more vulnerable, because of their low body weights and hand-to-mouth habits. These data have shown that ASGM wastes have the potential to cause harmful health effects in populations within mining communities. Therefore, characterisation and proper management of these wastes are necessary to ensure sustainable mining.